Authority of Deposit Insurance Corporation in Bank Guarantee and Resolutions Post Law Number 4 of 2023 Concerning Development and Strengthening of Financial Sector - Elyana Novira (Eduvest - Journal of Universal Studies, 2023)
In the banking world, the institution of LPS is strengthened because LPS is one of the supporters of economic stability, strengthening the authority of LPS in carrying out the functions of deposit guarantor and bank resolution, and a new mandate is also given to LPS as the organizer of the insurance policy guarantee program, then followed by an increase in supervisory and regulatory functions by the insurance supervision authority. The purpose of the study was to determine the nature of the existence of the Deposit Insurance Corporation, and to find out the Resolution of Failed Banks by LPS After the Issuance of the Law on the Development and Strengthening of the Financial Sector. The method used is the method of writing law. The government wants the P2SK Law to be the first step in financial sector reform. LPS is domiciled as part of the financial safety net that can minimize the adverse impact of the banking crisis. Another function and role played by LPS in shaping the stability of the banking system is to implement bank resolutions, both regarding failed banks that must be liquidated and those that must be saved.